Low Velocity Determination based on Seismic Tomography - Naser Mohmed Elzawam (Journal of Pure & Applied Sciences, 2017)
One of the main goals in seismic data processing is to estimate seismic velocities of geological structure in the earth. Structural velocities are needed for depth migration, the process that converts seismic data, recorded as a function of time, into a depth image of subsurface. Conventional velocity analysis methods generally assume flat layered geology and mild lateral velocity variation. In areas with structurally complex geology, these methods often fail, and more sophisticated techniques are required. One of these techniques, so called seismic tomography, compares observed traveltimes, measured for each source receiver experiment, with expected traveltimes, computed by ray tracing through an assumed velocity model, the differences are projected back over the traced ray paths to produce an update to the model. The velocity-depth determination method is demonstrated on a synthetic example.